Jitters on the Eve of the Great Recession: Is the Belief in Divine Control a Protective Resource?. (26th May 2021) - Upenieks, Laura; Schieman, Scott; Bierman, Alex
Abstract: One factor that has received surprisingly little attention in understanding the mental health consequences of the 2007–2008 financial crisis is religion. In this study, we ask: what is the relationship between two economic stressors—job insecurity and financial strain—and depression? And how do changes in religious belief, indexed by the sense of divine control, moderate those relationships? We use two waves of the U.S. Work, Stress, and Health (US-WSH) project (2005–2007), which occurred on the eve of the Great Recession. Results suggest that increases in job insecurity and financial strain are associated with increased levels of depression. However, those associations are (1) buffered among individuals who simultaneously increased in the sense of divine control and (2) exacerbated among individuals who decreased in the sense of divine control. Moreover, the buffering and exacerbating effects of divine control are significantly stronger among workers with lower levels of education.